FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN IMUNISASI TETANUS TOKSOID DUA (TT2) PADA IBU HAMIL TRIMESTER TIGA DI PUSKESMAS KEMUNING DESA CIMANGGIS KECAMATAN BOJONG GEDE KABUPATEN BOGOR PROVINSI JAWA BARAT 2016 - Nurmawati Nurmawati; Munawaroh Munawaroh (Jurnal Ilmu dan Budaya, 2017)
The background: Tetanus toxoid immunization is the process to build up immunity as a prevention against tetanus. There are 53 neonatal tetanus cases reported from 13 provinces with the number of 27 death cases or 50.9% CFR. Compared to 2014, a decline occurred in both the number of cases and the CFR, which are 84 cases out of 15 provinces with a CFR of 64.3%. Based on an overview of cases by birth attendant risk factors, 33 cases (62%) are helped by traditional birth attendants such as shamanic midwifes. By performing umbilical cord care, only 6 cases (11%) were treated using alcohol/iodine, while others used the traditional, others and unknown ways. The purpose of this study is to determine the factors associated with tetanus toxoid two (TT2) immunization on third trimester pregnant women at Puskesmas Kemuning, Cimanggis Village, Bojong Gede District, Bogor Regency, West Java Province in 2016. The study used cross sectional design. The population in this study were all third trimester pregnancy women at Puskesmas Kemuning, Cimanggis Village, Bojong Gede District, Bogor Regency, West Java Province in 2016. The total number of population from December 6 – January 3 were 45 women. The collection of data used in this study were primary data taken directly from the respondents using questionnaires by Chi-Square test. The result showed that as many as 23 of respondents (51.1%) are less knowledgeable, 26 of respondents (57.8%) received information from print media, 24 of respondents (53.3%) had no support from her husband and 27 of respondents (60.0%) had no availability of drugs. Variables that are related are knowledge (p = 0.017), information media (p = 0.014), the support of husband (p = 0.001), and the availability of drugs (p = 0.016) at Puskesmas Kemuning, Cimanggis Village, Bojong Gede District, Bogor Regency, West Java Province in 2016. Researchers suggest the need for similar studies with more complete and examine the different variables.